Structures of Rat and Human Islet Amyloid Polypeptide IAPP(1–19) in Micelles by NMR Spectroscopy - Nanga, Ravi Prakash Reddy (2008)
Disruption of the cellular membrane by the amyloidogenic peptide IAPP (or amylin) has been implicated in β-cell death during type 2 diabetes. While the structure of the mostly inert fibrillar form of IAPP has been investigated, the structural details of the highly toxic prefibrillar membrane-bound states of IAPP have been elusive. A recent study showed that a fragment of IAPP (residues 1–19) induces membrane disruption to a similar extent as the full-length peptide. However, unlike the full-length IAPP peptide, IAPP(1–19) is conformationally stable in an α-helical conformation when bound to the membrane. In vivo and in vitro measurements of membrane disruption indicate the rat version of IAPP(1–19), despite differing from hIAPP(1–19) by the single substitution of Arg18 for His18, is significantly less toxic than hIAPP(1–19), in agreement with the low toxicity of the full-length rat IAPP peptide. To investigate the origin of this difference at the atomic level, we have solved the structures of the human and rat IAPP(1–19) peptides in DPC micelles. While both rat and human IAPP(1–19) fold into similar mostly α-helical structures in micelles, paramagnetic quenching NMR experiments indicate a significant difference in the membrane orientation of hIAPP(1–19) and rIAPP(1–19). At pH 7.3, the more toxic hIAPP(1–19) peptide is buried deeper within the micelle, while the less toxic rIAPP(1–19) peptide is located at the surface of the micelle. Deprotonating H18 in hIAPP(1–19) reorients the peptide to the surface of the micelle. This change in orientation is in agreement with the significantly reduced ability of hIAPP(1–19) to cause membrane disruption at pH 6.0. This difference in peptide topology in the membrane may correspond to similar topology differences for the full-length human and rat IAPP peptides, with the toxic human IAPP peptide adopting a transmembrane orientation and the nontoxic rat IAPP peptide bound to the surface of the membrane.